2020
DOI: 10.1155/2020/9210572
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation May Decrease Thyroid Peroxidase Antibody Titer via Reducing Oxidative Stress in Euthyroid Patients with Autoimmune Thyroiditis

Abstract: Objective. Selenium, as an antioxidant, has been implicated in the development of autoimmune thyroiditis (AIT). Many studies showed selenium supplementation could decrease thyroid autoantibodies in patients with AIT. However, the underlying mechanisms have not been well determined. Therefore, we performed a clinical study to investigate the possible mechanism of beneficial effects of selenium treatment on AIT patients. Methods. Forty euthyroid patients with AIT were randomized into two groups. Group I was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…intervention in the first group. The authors concluded that Se alleviates the thyroid autoimmune process by improving body antioxidative status [31]. Se supplementation (60 and 180 μg/day) significantly reduced proinflammatory cytokine release mediated by INF-g (CXCL-9 and 10) in AIT euthyroid females who were not treated with LT4 in comparison to the placebo group.…”
Section: Reviewmentioning
confidence: 98%
“…intervention in the first group. The authors concluded that Se alleviates the thyroid autoimmune process by improving body antioxidative status [31]. Se supplementation (60 and 180 μg/day) significantly reduced proinflammatory cytokine release mediated by INF-g (CXCL-9 and 10) in AIT euthyroid females who were not treated with LT4 in comparison to the placebo group.…”
Section: Reviewmentioning
confidence: 98%
“…Moreover, TPOAb and TgAb decreased after six months of Se supplementation compared with baseline [ 87 ]. Tian et al confirmed that Se supplementation decreased TPOAb titer by enhancing defense against oxidative stress in euthyroid patients with AIT [ 30 ]…”
Section: Micronutrients In Htmentioning
confidence: 99%
“…In addition to the use of LT4, an appropriate diet and supplementation may be an important aspect of the treatment process. Se supplementation is associated with a significant decrease in TPOAb [ 30 , 31 ]. On the other hand, inadequate dietary Se intake may exacerbate HT [ 2 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that selenium administration can help individuals with autoimmune thyroiditis reduce thyroid autoantibodies. Selenium therapy has been shown to lower TPO antibody titers in euthyroid individuals with autoimmune thyroiditis by strengthening the defense against oxidative stress and scavenging free radicals [ 86 ].…”
Section: The Role Of Tpo and Lox In Thyroid Oxidative Stress And Modu...mentioning
confidence: 99%